Case Report: Endoscopic evacuation of a large cerebellar hemorrhage in a term newborn—a modified approach using an agitation wire enhanced suction device - Wendel, C.; Ganslandt, O.; Rafat, N.; Bittl, M. (Frontiers in Surgery, 2025)
BackgroundCerebellar hemorrhage in term newborns is a rare but potentially life-threatening condition requiring prompt intervention. Traditional micro surgical approaches carry significant risks of surgical trauma and post-operative cerebrospinal fluid leakage.Case descriptionWe present a case of successful endoscopic evacuation of a large cerebellar hemorrhage using a novel suction device with an integrated agitation wire. Complete hematoma evacuation was achieved through a single burr hole approach.ConclusionAt 12-month follow-up, developmental assessment demonstrated excellent neurological outcome with no evidence of hydrocephalus, suggesting this minimally invasive technique as a viable alternative to traditional approaches.